Recent Investigation on Fuels, EV and Hybrid Electrical Vehicles impacts on Pollution Control Techniques and Predictions Using IOT Technology - N.Sirisha, Brahmani Cherukuru, Venkata Sai Shalini Ganni, Middela Ashna Reddy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
As there is a growing rate of urbanization it is no new news that our world is being affected by global warming which is majorly caused by automobiles and its pollution taking their first spot and the rest settling down to their lower ranks. Evolvement in automobiles like electrical and hybrid electrical vehicles had lead to ease in day to day activities at the same time there is an increase in direct and life cycle emissions. In recent years people have shown interest towards developing IOT, it helps in monitoring and detecting the emissions and involve wireless sensors and gas sensors. The detected emission results are transferred to the database using the internet. The scope of this paper is to give an overview of predictions and control techniques of pollutions caused by vehicles using the IOT technology. IOT helps in acquiring and refining the result, it is an efficient and effective way to determine the pollutants compared to other methods and it is economical than other methodologies. Finally the main objective is to find a solution for environmental pollution.